FTO demethylase activity is essential for normal bone growth and bone mineralization in mice - Sachse, G; Church, C; Stewart, M; Cater, H; Teboul, L; Cox, RD; Ashcroft, FM (Elsevier, 2017)
The Fto gene locus has been linked to increased body weight and obesity in human population studies, but the role of the actual FTO protein in adiposity has remained controversial. Complete loss of FTO protein in mouse and of FTO function in human patients has multiple and variable effects. To determine which effects are due to the ability of FTO to demethylate mRNA, we genetically engineered a mouse with a catalytically inactive form of FTO. Our results demonstrate that FTO catalytic activity is not required for normal body composition although it is required for normal body size and viability. Strikingly, it is also essential for normal bone growth and mineralization, a previously unreported FTO function.